PENERAPAN PEMBELAJARAN KARAKTER KELAS PADA MATA KULIAH AKUNTANSI BIAYA - Riadi, RM (Jurnal Akuntansi (Media Riset Akuntansi & Keuangan), 2013)
This research is classroom action research. This research consist of 2 cycle and everycycle consist of 2 meeting. This research aimed to know whether classroom characterlearning can implemented according direct instruction. Object this research are studentabout 38 students who has follow Cost Accounting. From the results of the first cycle canbe seen that individual mastery has not happened. This is due to the persistence ofstudents who do not understand and unpreparedness of the students themselves. In thesecond cycle has occurred completeness individually, it is because of the firmness oflecturers in the form of sanctions and rewards to students. In the classical completenessincrement cycle has not occurred, it is because there are many students who are notcompletely implement the learning process so that the timing of the task did notunderstand implement. In the second cycle occurs classical completeness, this isbecause students interested in the materials provided, so that the interest andenthusiasm students so well. Value of the character generated is also quite good,although the first cycle, the first meeting, the value of honesty and responsibility is notgood enough. Based on the results of the implementation of direct teaching-based CostAccounting courses can be concluded that the Character Class character education canbe applied konsissten especially in Cost Accounting courses, so as to combineaccounting skills with other disciplines that will be able to provide supplies for students toenter the world employment.Keyword : learning character cycle, classical completenes